(untitled) (Heritage, 2022)
The development of information and communication technologies has led to the accelerated development of society, but with the facilitation of communication, business and entertainment, there have been a number of problems regarding the security of users in cyberspace, but also the states themselves. Cybercrime has become a frequent occurrence that causes material and non-material damage to social media users who are often insufficiently informed about the methods of such cybercriminals. On the other hand, the virtual environment has enabled cyber terrorists to transfer their motives and activities from physical to digital space. Unfortunately, the consequences of such cyber-terrorist activities are no less devastating than in traditional terrorist activities. Hidden in the digital space, terrorists propagate their political or religious ideology, recruit new members and organize attacks, using, often with great success, identical terrorist strategies that were used before cyberspace. The lack of international cooperation, harmonization of legislation, but also the neglect of security systems of new devices by experts in this field, which function with the help of information and communication technologies, will create even more fertile ground for the continuation and development of such criminal activities. Unfortunately, not all countries are motivated or see their interests in terms of cooperation in this area, but the destructive potential of cybercrime and cyber terrorism at the global level must be a strong enough factor to make full international cooperation in this area imperative.